Added value of teaching factory learning in services production unit to prepare graduate work readiness - Rosidah Rosidah; Sutirman Sutirman (Jurnal Cakrawala Pendidikan, 2023)
Teaching Factory (TEFA) Learning Model is a means of improving students' skills to meet the qualifications required by the workplace. There is a discrepancy between the output performance criteria of vocational school graduates and the job qualifications required in the industry. The industrial world is rapidly advancing in technology and information, while schools are struggling to provide adequate laboratory and practical facilities. This study examined the students’ perspectives on TEFA learning in service production units in vocational schools to prepare them considering graduate work readiness (GWR). The research employed a descriptive qualitative approach with the data collection techniques utilizing in-depth interviews and observations. The research participants were students at vocational schools joining the TEFA teaching and learning program. The collected data were then validated using source triangulation. The data analysis followed a qualitative method with an interactive model as realized in several stages: data collection, data reduction, data display, and conclusions.  The findings showed that students' perspectives on TEFA learning inform added values in 3 domains: 1) knowledge, 2) skills, and 3) attitudes. Furthermore, TEFA learning provided students with the necessary competencies which align with the performance criteria required by the industry, boosted their self-confidence and learning motivation, and fostered a mental attitude of independence, responsibility, and self-efficacy in meeting industrial needs.